PENINGKATAN PELUANG KERJA BAGI MASYARAKAT LOKAL MELALUI PENGEMBANGAN EKOWISATA DI TAMAN NASIONAL GUNUNG CIREMAI - Diah Zuhriana; Hadi S. Alikodra; Soeryo Adiwibowo; Hartisari S. (Media Konservasi, 2013)
Community-based ecotourism become a very important development, especially in national park area that is prone to disruption surrounding communities. Illegal activities of the national parks can be stopped more effectively if they are given alternative employment opportunities. Ciremai Mountain National Park (TNGC) has 19 natural tourism objects that can be developed to enhance employment opportunities and income of the people who live around the area. The study was conducted at the National Park Mount Ciremai (TNGC) Kuningan regency of West Java Province. This study aims to analyze the employment opportunities for local communities through tourism development, particularly the development of business in the tourism sector. Data analysis was performed with the approach supply and demand. The results showed that through the development of business types that already exist in the tourism sector to increase employment opportunities for local communities of 41.46%, and for the amount of new business units increased by 33.72% with an estimated increase in employment opportunities for the local communities at 24.65 %. Keywords: employment, Gunung Ciremai National Park, tourism, communities